LEGAL ASSISTANCE IN APPLICATION OF BUSINESS PERMIT IN ONLINE SINGLE SUBMISSION SYSTEM (OSS) AT KANTOR NOTARIS & PPAT RIAN SUGITO, SH., M.Kn. - Sheerleen Sheerleen; Winda Fitri (ConCEPt - Conference on Community Engagement Project, 2022)
Indonesian government concentrated enough to support the growth of businesses in Indonesia to support the enhancement of economy. As the number of businessperson grows, the government shall also balance them with a proper system with the goal of to create a good governance and make it happen. This is what then inspires the birth of e-government. With that, the government has started to make changes and fixing on the available system. One of the most important factor in attracting business persons from within or out of the country is the efficiency and feasibility to acquire permit to conduct businesses and operational permit and get the business number. With the execution of e-government, the one that relates to business number is the establishment of Peraturan Pemerintah No. 24 tahun 2018 tentang Pelayanan Perizinan Berusaha Terintegrasi secara Elektronik atau Online Single Submission. The goal of the regulation is to minimize the error and frauds that could possibly happen within the process of managing the permit. The existence of the OSS is expected to achieve the government’s goal to ease the access for businesspersons and create a good governance. However, within its application there are several issues due to the lack of information and comprehension of users. With that being said, the author will conduct a legal assistance to process Business permits within the OSS at Kantor Notaris & PPAT Rian Sugito, SH., M.Kn.as the partner of the aactivity. The assistance will be done by conducting interview on the notary and the staffs.